2020
DOI: 10.1039/c9cc09080k
|View full text |Cite
|
Sign up to set email alerts
|

Complete identification of all 20 relevant epimeric peptides in β-amyloid: a new HPLC-MS based analytical strategy for Alzheimer's research

Abstract: Although the underlying cause of Alzheimer's disease (AD) is not known, detection of racemization/isomerization of Asp and Ser in β-amyloid (Aβ) may be crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“… 35–39 Chiral chromatography was shown to separate synthetic Aβ epimers and isomers containing Asp and Ser residues. 40 Ion mobility separation-mass spectrometry (IMS-MS) is a powerful tool for the analysis and characterization of isomerized and epimerized peptides in the gas phase. 41–45 Recently, synthetic tryptic Aβ peptide isomers have been shown to resolve in IMS-MS using structures for lossless ion manipulations (SLIM).…”
Section: Introductionmentioning
confidence: 99%
“… 35–39 Chiral chromatography was shown to separate synthetic Aβ epimers and isomers containing Asp and Ser residues. 40 Ion mobility separation-mass spectrometry (IMS-MS) is a powerful tool for the analysis and characterization of isomerized and epimerized peptides in the gas phase. 41–45 Recently, synthetic tryptic Aβ peptide isomers have been shown to resolve in IMS-MS using structures for lossless ion manipulations (SLIM).…”
Section: Introductionmentioning
confidence: 99%
“…With this approach, various enzymes or a combination of enzymes with different amino acid enantiomers at specific cleavage sites can be used. As an example, trypsin in association with endoproteinase Asp-N (cleavage at N-terminus L-Asp) [63], L-isoaspartyl methyltransferase (PIMT) (methylation of L-isoAsp) [14,32,35,37,63] and Daspartyl endoproteinase (DEAP) also named paenidase (cleavage at C-terminus D-Asp) [64] can recognize only L-α-Asp, L-β-Asp and D-α-Asp residues respectively. Other proteases can be used to cleave proteins at specific sites, such as glutamyl endoproteinase Glu-C (cleavage at C-terminus L-Glu) for histone H2B [32] and human immunoglobulin G kappa chain [15] analyses.…”
Section: Determination Of Chiral Protein Sequencesmentioning
confidence: 99%
“…On the separation front, 2-D reversed-phase LC and chiral LC have demonstrated capabilities to resolve peptide epimers. In a recent example, 20 epimers of amyloid β (Aβ) (1–42) peptide were completely resolved by a MS-compatible chiral chromatography method after the sample was digested with trypsin .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…On the separation front, 2-D reversed-phase LC and chiral LC have demonstrated capabilities to resolve peptide epimers. In a recent example, 20 epimers of amyloid β (Aβ) (1–42) peptide were completely resolved by a MS-compatible chiral chromatography method after the sample was digested with trypsin . This example suggested that combination of enzymatic digestion and an optimized chiral LC method could be a general approach to completely resolve epimers of large peptides prior to MS analysis.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation